Chemomechanische Modellierung der Wärmebehandlung von Stählen mit der Phasenfeldmethode - Schoof, Ephraim (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
The development of high-strength steels can be accelerated using numerical methods. In particular, the phase-field method has emerged as a powerful tool to describe the microstructure evolution on the mesoscopic length scale. In the present work, multiphase-field models are presented to numerically display the morphological evolution during the heat treatment of steel.